2016
DOI: 10.18632/oncotarget.10984
|View full text |Cite
|
Sign up to set email alerts
|

Healthy CD4+ T lymphocytes are not affected by targeted therapies against the PI3K/Akt/mTOR pathway in T-cell acute lymphoblastic leukemia

Abstract: An attractive molecular target for novel anti-cancer therapies is the phosphatidylinositol 3-kinase (PI3K)/Akt/mammalian target of rapamycin (mTOR) pathway which is commonly deregulated in many types of cancer. Nevertheless, the effects of PI3K/Akt/mTOR inhibitors on T lymphocytes, a key component of immune responses, have been seldom explored. In this study we investigated the effects on human CD4+ T-cells of a panel of PI3K/Akt/mTOR inhibitors: BGT226, Torin-2, MK-2206, and ZSTK474. We also assessed their ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 65 publications
0
14
0
Order By: Relevance
“…Compared to Torin-1, bioavailability, metabolic stability and plasma exposure was significantly improved [50]. Moreover, it has been shown that Torin-2 induces a strong cytotoxic effect on T-ALL cells and stimulated T lymphocytes whereas it did not affect the viability of quiescent healthy CD4 + T lymphocytes [51]. Therefore, Torin-2 rather preserves the immune system during molecular targeted anti-cancer therapy in contrast to the well-known immunosuppressive properties of Rapamycin that is broadly applied for prevention of acute rejection in transplant patients [36].…”
Section: Discussionmentioning
confidence: 99%
“…Compared to Torin-1, bioavailability, metabolic stability and plasma exposure was significantly improved [50]. Moreover, it has been shown that Torin-2 induces a strong cytotoxic effect on T-ALL cells and stimulated T lymphocytes whereas it did not affect the viability of quiescent healthy CD4 + T lymphocytes [51]. Therefore, Torin-2 rather preserves the immune system during molecular targeted anti-cancer therapy in contrast to the well-known immunosuppressive properties of Rapamycin that is broadly applied for prevention of acute rejection in transplant patients [36].…”
Section: Discussionmentioning
confidence: 99%
“…The PI3K/AKT/mTOR pathway is an important target due to its regulatory role in various cancers [24, 56, 57]; it is also involved in the invasion and metastasis and progression of hepatocellular carcinoma, cervical cancer, and LC [22, 25, 58]. ERS shares a correlation with the PI3K/Akt/mTOR signaling pathway.…”
Section: Discussionmentioning
confidence: 99%
“…One recent study did demonstrate that 48h exposure of normal unstimulated T lymphocytes to MK-2206 showed very limited loss of viability to these resting cells (about 10% loss). In contrast, T cells treated with mitogen in the presence of MK-2206 were more sensitive, with recorded viabilities at a bit less than 70% compared with controls [40]. Thus cellular activation in the presence of Akt inhibition appeared somewhat toxic to T cells.…”
Section: Discussionmentioning
confidence: 83%